Irén Dobos horticulturalist-teacher plant protection engineer expert awarded by Antal Gulyás medallion for crop protection" in 2015 (laudation) - Radócz, László; Tarcali, Gábor; Szabóné Asbolt, Tünde; Kövics, György; Kiss, László (Acta Agraria Debreceniensis, 2015)
The Public Utility for Development of Crop Protection Teaching (NOFKA) and The Hajdú-Bihar County Regional Association of Hungarian Chamber of Crop Protection Specialists and Plant Doctors established a joined Award Committee in 2011, which intend to serve as moral appreciation to prominent persons with excellent achievements by awarding the „Antal Gulyás medallion for crop protection” which are available for outstanding teachers, researchers, and practical crop protection specialists. In 2015 dr. Irén Dobos horticulturist- teacher and plant doctor has been decorated with the „Antal Gulyás medallion for crop protection” for her “excellence in integrated plant protection practical research activity and effective knowledge transfer”.